(untitled) (Tanzania Journal for Population studies and Development, 2025)
Carbon trading projects are widely promoted as effective climate mitigation tools, and are often lauded for their potential to alleviate poverty and improve livelihoods. They are intended to significantly reduce deforestation and forest degradation, and improve livelihoods forrural forest-dependent communities. This article explores the socio-economic effects of a carbon trading project on the local community in two villages—Mongo wa Mono andYaeda Chini—in Mbulu District, Tanzania. The study was guided by the theory of change, which suggests that a project involves processes and outcomes for a local community throughout its lifecycle. The study employed a descriptive design, using both qualitative and quantitative methods. Data was collected through semi-structured interviews (n=91), in-depth interviews (12 participants), 2 focus group discussions, documentary reviews, and field observation. The findings revealed several positive outcomes of the project, including financial benefits to local communities through cash payments that are used to improve the education infrastructure and healthcare facilities. The youth have also been employed as game scouts. As well, the project has improved natural resource conservation and environmental restoration. The article emphasizes the importance of collaborative environmental conservation in carbon trading initiatives to ensure sustainable and equitable benefits for local communities. It highlights multiple benefits of carbon trading projects, which are crucial for policymakers, environmental organizations, and future projects to achieve sustainable climate solutions.